1990
DOI: 10.1111/j.1469-8749.1990.tb08120.x
|View full text |Cite
|
Sign up to set email alerts
|

Deficits in Reciprocal Inhibition of Children With Cerebral Palsy as Revealed by H Reflex Testing

Abstract: SUMMARY Experiments were performed to determine whether spinal and supraspinal components of reciprocal inhibition (a neural mechanism responsible for the prevention of muscular co‐ordination during voluntary movement) were present in groups of non‐disabled children and children with cerebral palsy. Changes in the gastrocnemius‐soleus H reflex were examined during voluntary dorsiflexion and plantarflexion of the ankle and during a vibration applied to the anterior tibial tendon. The results indicate that child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
0
1

Year Published

1992
1992
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(53 citation statements)
references
References 32 publications
4
48
0
1
Order By: Relevance
“…Characteristically, children with diplegia had more than double, and children with hemiplegia had close to double, the co-activity of the comparison children. The high degree of co-activity in children with CP could be caused by a disturbance in reciprocal inhibition, resulting in co-activation during voluntary movements, 25 or aberrant corticospinal projections making isolated muscle control difficult. 26,27 Higher amplitudes of co-activation were seen in the children with diplegia than in those with hemiplegia.…”
Section: Discussionmentioning
confidence: 99%
“…Characteristically, children with diplegia had more than double, and children with hemiplegia had close to double, the co-activity of the comparison children. The high degree of co-activity in children with CP could be caused by a disturbance in reciprocal inhibition, resulting in co-activation during voluntary movements, 25 or aberrant corticospinal projections making isolated muscle control difficult. 26,27 Higher amplitudes of co-activation were seen in the children with diplegia than in those with hemiplegia.…”
Section: Discussionmentioning
confidence: 99%
“…Alternating limb movements are particularly difficult for children with CP. 14,16 The challenge is to control Ia inhibitory interneurons which receive direct input from muscle stretch receptors. 22 Inhibition of soleus motoneurons via these pathways comes into play especially when descending steps.…”
Section: Discussionmentioning
confidence: 99%
“…To avoid causing participants stress, possibly affecting supraspinal control, 16 they were not specifically encouraged to make maximum movements.…”
Section: Massagementioning
confidence: 99%
“…We suggested that the latter result was either due to a general disturbed motor output (for example, Leonard et al 1990, Neilson et al 1990, or an indistinct internal representation based on disturbed sensory input. However, we were unable to differentiate between these two possibilities based on our data.…”
Section: Bilateral Transfer Of Sensory Informationmentioning
confidence: 98%